ANALYSIS OF THE EPIZOOTIC SITUATION OF ANIMAL BRUCELLOSIS IN THE FERGANA VALLEY (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2025)
The scientific research was aimed at analyzing the epizootic situation of brucellosis in certain farms of the Fergana Valley. The studies were conducted in the farms “Baxt Imkon Rivoji” of Oltinko‘l district and “Muqumiy” of Andijan district in Andijan region, as well as “Zotdor Chorva Davri” of Kuva district and “Khamzayev Bekzod Chorvasi” of Furqat district in Fergana region. A total of 234 blood samples were collected from 3,650 cattle. In the Rose Bengal test, 32 blood samples tested positive, while 202 samples tested negative. When the 32 Rose Bengal positive samples were reexamined using the agglutination reaction (AR), all 32 samples showed negative results.